2007
DOI: 10.1039/b615369k
|View full text |Cite
|
Sign up to set email alerts
|

Use of porous anodic alumina membranes as a nanometre-diameter column for high performance liquid chromatography

Abstract: The possibility of using porous anodic alumina membranes as a column for normal-phase high performance liquid chromatography was evaluated using phenol and toluene with mobile phases having different solvent compositions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 26 publications
(26 reference statements)
4
15
0
Order By: Relevance
“…Their unique uniform pores ranging from a few to tens nm in diameter and stability in organic and inorganic solution phases could shed light on a plethora of different promising applications such as size-exclusive separation (Yamaguchi et al, 2004;El-Safty et al, 2010;Mekawy, 2011), enzymatic nanoreactors (Fu et al, 2008Mekawy et al, 2011, sensors (El-Safty et al, 2008a,b) and nanofluidic devices (Yamashita et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Their unique uniform pores ranging from a few to tens nm in diameter and stability in organic and inorganic solution phases could shed light on a plethora of different promising applications such as size-exclusive separation (Yamaguchi et al, 2004;El-Safty et al, 2010;Mekawy, 2011), enzymatic nanoreactors (Fu et al, 2008Mekawy et al, 2011, sensors (El-Safty et al, 2008a,b) and nanofluidic devices (Yamashita et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have been reported that the AAO membrane could be used as a membrane itself (without etching process) [18,19]. As a filter, the AAO membrane provides uniform channels, facile controllable pore size and large surface area.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their uniform pores, ranging from a few to tens of nanometers, and their hydrothermal stability in organic and inorganic solution phases, nanoporous materials have been anticipated for size-exclusive separation [4], enzymatic nanoreactors [5], sensors [6], and nanofluidic devices [7]. Since the fabrication of the classic MS41 nanomaterials [1a], significant effort has been expended in creating new levels of hierarchical materials with controlled structural geometry, mesophase morphology, and mesopore size and shape by varying the surfactant templates and synthesis conditions [1][2][3].…”
Section: Introductionmentioning
confidence: 99%